CZYNNIKI EKONOMICZNE A POZIOM PRZESTĘPCZOŚCI – BADANIE EKONOMETRYCZNE - Bieniek, Piotr; Cichocki, Stanisław; Szczepaniec, Maria (Zeszyty Prawnicze, 2016)
ECONOMIC FACTORS AND CRIME INDICATORS – AN ECONOMETRIC MODEL Summary The paper is an attempt to investigate the relationship between some economic factors and crime indicators using an econometric model. Sociological determinants i.e. the number of divorces or the number of pupils in secondary schools are also included. The model investigates the influence of some variables on crime indicators at the level of powiats. The model includes all types of crimes without differentiating between them.